The Role of the Education Quality Assurance System in Improving School Education Quality: Supporting Factors and Barriers to Success - Wahid Hasyim; Mohammad Makinuddin; Muhammad Muizzuddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Education quality assurance is one of the strategic instruments for realizing quality and competitive education. The education quality assurance system is designed to ensure that the entire process of educational provision runs in accordance with established standards and undergoes continuous improvement. This library research aims to analyze the system and role of education quality assurance in improving school education quality, as well as to identify the factors that support and hinder its successful implementation. The findings show that the education quality assurance system plays an important role in improving the quality of learning, the effectiveness of school management, teacher professionalism, a culture of quality, and the accountability of educational institutions. The success of quality assurance implementation is influenced by leadership commitment, human resource competence, the availability of facilities and infrastructure, organizational culture, and stakeholder support. Conversely, limited understanding of the concept of quality, budgetary constraints, resistance to change, weak supervision, and excessive administrative burden constitute the main inhibiting factors. Synergy among all parties is therefore required so that the education quality assurance system can operate effectively and sustainably.